2013
DOI: 10.1111/let.12030
|View full text |Cite
|
Sign up to set email alerts
|

Do predatory drill holes influence the transport and deposition of gastropod shells?

Abstract: L.R. 2013: Do predatory drill holes influence the transport and deposition of gastropod shells? Lethaia, Vol. 46, Predatory gastropod drill holes are an abundant and easily identifiable signal of predation in ancient and modern molluscan shell assemblages. Many workers have used drill holes to interpret patterns of predation intensity and success in fossil assemblages. These studies are predicated on the assumption that the relative abundances of drilled and undrilled shells in an assemblage accurately reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Additionally, drilling frequency can be affected by hydrodynamic differences between drilled and undrilled shells. A number of experimental studies have demonstrated that drilled shells entrain at lower velocities than undrilled shells of the same species (Chattopadhyay et al, 2013b;Lever et al, 1961; but see Molinaro et al, 2013). Chattopadhyay et al (2013b) also demonstrated that the position of the drill hole dictates the entrainment velocity, implying possible sorting based on stereotypic drill-hole site selection by the driller.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, drilling frequency can be affected by hydrodynamic differences between drilled and undrilled shells. A number of experimental studies have demonstrated that drilled shells entrain at lower velocities than undrilled shells of the same species (Chattopadhyay et al, 2013b;Lever et al, 1961; but see Molinaro et al, 2013). Chattopadhyay et al (2013b) also demonstrated that the position of the drill hole dictates the entrainment velocity, implying possible sorting based on stereotypic drill-hole site selection by the driller.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Fossil assemblages, even when collected in bulk or otherwise (Ottens et al 2012) to avoid collection bias, still show various types of preservation biases (Kidwell 2002). These include (nonexhaustively): preferential preservation of larger, more robust individuals; hydrodynamic sorting through transport (Molinaro et al 2013; Chattopadhyay et al 2013a,b) and nonuniform sampling of living populations (e.g., fossilization of organisms where young and adults live in different environments), with the general tendency being to remove smaller specimens from the record, as shown by Cooper et al (2006). Museum collections, suffering from both biostratinomic and collection bias, are likely to be particularly unrepresentative.…”
Section: Practical Problemsmentioning
confidence: 99%
“…Drilled gastropod shells do not have the same proclivity for fluid transport because the drill hole is often rotated to the underside of shells resting on the seafloor (Molinaro et al, 2013). A potential bias that has been considered less often is fragmentation of undrilled shells by shellcrushing predators, which would have the opposite effect on drilling frequency, by removing undrilled shells (Ansell and Morton, 1985;Harper et al, 1998;Kelley and Hansen, 2003).…”
Section: Biases Of Drilling Intensitymentioning
confidence: 99%